2015
DOI: 10.15690/vramn.v70.i5.1445
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Factors of Male Infertility

Abstract: В настоящее время проблемы здоровья населения стра-ны, рождаемости и перспективы демографии -ключевые не только в России, но и за рубежом. Неблагоприятные демографические показатели с устойчивым отрицательным коэффициентом естественного прироста населения в по-следние десятилетия заставляют специалистов различного профиля (генетиков, морфологов, иммунологов, эндокри-нологов, гинекологов, урологов) обратиться к анализу фак-торов, влияющих на рождаемость, среди которых важное место занимает бесплодие [1][2][3]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…Recent epidemiological data has shown that approximately 15% of married/unmarried couples are affected by infertility for which only 40-50% cases are attributable to male infertility [26] which itself could be due to either azoospermia or erectile dysfunction [27]. Identifiable factors (reversible/irreversible) influencing male fertility as reported by previous studies include drugs (such as anabolic steroid, replacement testosterone, and opiates), testicular varicocele, undescended testes, urinary tract infections, testicular tumor, hormonal imbalances, premature or retrograde ejaculation, prolonged heat exposure, obesity, older age, cigarette smoking, alcohol, heavy metals, pesticides, oxidative stress, genetic factors, and different environmental and nutritional factors [28–34]. Thus, in managing male infertility, treatment plans are designed alongside the identifiable possible cause and these interventions could be either medical or surgical [27, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological data has shown that approximately 15% of married/unmarried couples are affected by infertility for which only 40-50% cases are attributable to male infertility [26] which itself could be due to either azoospermia or erectile dysfunction [27]. Identifiable factors (reversible/irreversible) influencing male fertility as reported by previous studies include drugs (such as anabolic steroid, replacement testosterone, and opiates), testicular varicocele, undescended testes, urinary tract infections, testicular tumor, hormonal imbalances, premature or retrograde ejaculation, prolonged heat exposure, obesity, older age, cigarette smoking, alcohol, heavy metals, pesticides, oxidative stress, genetic factors, and different environmental and nutritional factors [28–34]. Thus, in managing male infertility, treatment plans are designed alongside the identifiable possible cause and these interventions could be either medical or surgical [27, 35].…”
Section: Discussionmentioning
confidence: 99%
“…About 20–30% of infertility is caused by male factors [ 31 ]. The sex chromosomes (X and Y) in men play key roles in germ cell development.…”
Section: Discussionmentioning
confidence: 99%
“…It affects 10-15% of couples in reproductive age (Winters & Walsh, 2014). Some studies show that environmental, physiological and genetic factors are related to 25% of male factor infertility due to semen quality, including oxidative stress, which has frequently been associated with the problem (Kolesnikova et al, 2015;Aitken, 2016).…”
Section: Introductionmentioning
confidence: 99%